Synthesis of Indenoquinoxalinone-5-(furano, pyrano, and oxepino)spiro Ethers from Alkenylated Propargyl Ethers of Indenoquinoxalinone via Ring-Closing Enyne Metathesis - Padmashrija, Ammundi Jayavel Chirranjeevi; Kannadasan, Sathananthan; Shanmugam, Ponnusamy (Synlett, 2025)
A facile and efficient synthetic route for indenoquinoxalinone spiro-oxacyclic systems with small to medium ring sizes has been developed via an efficient ring-closing enyne metathesis (RCEYM) as a key step. The starting material O-alkylated propargylic alcohol of indenoquinoxalinone is synthesized via a two-step protocol: 1. propargylation of ketone followed by 2. alkenylation of the resulting propargyl ethers with alkenyl bromides. Upon being subjected to RCEYM using Grubbs II catalyst, the resulting O-alkenylated propargyl derivative furnished the spiro-ethereal products in good yield. Spectroscopic data and single-crystal XRD analysis characterized the structures of the products. A plausible mechanism is provided.
Keywords: ring-closing enyne metathesis; indenoquinoxalinone; alkenyl ether; Grubbs II catalyst; oxacyclic spiro compounds